Nanospray Drying as a Novel Technique for the Manufacturing of Inhalable NSAID Powders - Aquino Rita Patrizia; Stigliani Mariateresa; Del Gaudio Pasquale; Mencherini Teresa; Sansone Francesca; Russo Paola (The Scientific World Journal)
The aim of this research was to evaluate the potential of the nanospray drier as a novel apparatus for the manufacturing of a dry powder for inhalation containing ketoprofen lysinate, a nonsteroidal anti-inflammatory drug able to control the inflammation in cystic fibrosis patients. We produced several ketoprofen lysinate and leucine powder batches by means of nanospray dryer, studying the influence of process parameters on yield, particle properties (size distribution and morphology), and, mainly, aerodynamic properties of powders. Micronized particles were prepared from different hydroalcoholic solutions (alcohol content from 0 to 30% v/v) using ketoprofen in its lysine salt form and leucine as dispersibility enhancer in different ratios (from 5 to 15% w/w) with a total solid concentration ranging from 1 to 7% w/v. Results indicated that the spray head equipped with a 7 µm nozzle produced powders too big to be inhaled. The reduction of nozzle size from 7 to 4 µm led to smaller particles suitable for inhalation but, at the same time, caused a dramatic increase in process time. The selection of process variables, together with the nozzle pretreatment with a surfactant solution, allowed us to obtain a free flowing powder with satisfying aerosol performance, confirming the usefulness of the nanospray drier in the production of powder for inhalation.